2005
DOI: 10.1185/030079905x61839
|View full text |Cite
|
Sign up to set email alerts
|

Safety assessment of raloxifene over eight years in a clinical trial setting

Abstract: These 8-year data support the known clinical safety profile of raloxifene, established in the MORE trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 15 publications
1
66
1
1
Order By: Relevance
“…Raloxifene is a clinically-validated SERM, which has been shown to mimic the protective effect of estrogen on the skeletal system without triggering the proliferative effects of estrogen on the breast and endometrium of the uterus [4,5]. Many clinical studies have confirmed the therapeutic effectiveness of raloxifene in reducing the risk of vertebral fractures in postmenopausal osteoporosis patients by significantly slowing bone turnover, preventing bone loss, and maintaining the structural integrity of cancellous bone [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Raloxifene is a clinically-validated SERM, which has been shown to mimic the protective effect of estrogen on the skeletal system without triggering the proliferative effects of estrogen on the breast and endometrium of the uterus [4,5]. Many clinical studies have confirmed the therapeutic effectiveness of raloxifene in reducing the risk of vertebral fractures in postmenopausal osteoporosis patients by significantly slowing bone turnover, preventing bone loss, and maintaining the structural integrity of cancellous bone [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] Raloxifene is known to be a safe agent. [13] In our study, it did not induce any appreciable nephrotoxicity in therapeutic doses. Many studies have shown that raloxifene has also a favorable impact on lipid metabolism.…”
mentioning
confidence: 73%
“…[11,12] Clinical data suggest that raloxifene has a safety profile. [13] Oral bisphosphonates are an effective alternative to hormone replacement therapy in the management of postmenopausal osteoporosis and are becoming widely used as first choice treatment. Both second-and third-generation bisphosphonates, like alendronate and risedronate, are available as weekly tablets, which have facilitated the patient compliance to treatment together with a decreased occurrence of gastrointestinal side effects.…”
Section: B Yanik Et Almentioning
confidence: 99%
“…Goldstein et al (2000) reported that raloxifene was not increasing the incidence of endometrial cancer. Martino et al (2005) studied the safety of raloxifene over 8 years in a clinical trial setting. The authors reported that 8-year data support the known clinical safety profile of raloxifene.…”
Section: Raloxifenementioning
confidence: 99%